Real-Time Trajectory Tracking Control of a DC Motor Using a Self-Tuning Regulator with Online Parameter Estimation - Quang-Thien Nguyen; Hoang-Linh Le; Anh-Huy Nguyen; Duc-Anh-Quan Nguyen; Van-Dong-Hai Nguyen; Minh-Tam Nguyen; Van-Hiep Nguyen; Thanh-Binh Nguyen; Phuong-Quang Nguyen; Thi-Hong-Lam Le; Binh-Hau Nguyen; Dinh-Minh Vu (Control Systems and Optimization Letters, 2026)
An adaptive Self-Tuning Regulator (STR) is developed for DC motor control to address performance degradation caused by load disturbances and parameter uncertainties. The method combines online system identification using recursive least squares (RLS) with automatic controller retuning in discrete time. The motor dynamics are continuously estimated and used to update the controller parameters through a pole-placement (or minimum-variance) design, thereby maintaining the desired closed-loop response without manual gain adjustment. The STR is implemented in real time and tested under speed reference changes and varying load torque. Results confirm that the proposed approach enhances tracking performance and disturbance rejection compared with conventional fixed-gain control, making it suitable for practical DC drive systems operating under changing conditions.